Analisis Tokoh Kartini dalam Teori Bandura - Bintang Anugrah; Mutiara Anggi Pratiwi (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
This research aims to analyze the personality of R.A. Kartini using Albert Bandura's social learning theory, focusing on the concepts of reciprocal determinism, cognition and self-regulation, self-efficacy, self-system, and the stages of learning through behavior. Kartini, a figure who advocated for gender equality and women's education, displayed a strong intrinsic drive despite facing social and cultural barriers. Through Bandura’s theory, this study explores how Kartini’s social environment, internal values, and life experiences influenced her efforts in creating social change. The findings show that Kartini's personality reflects a complex interaction between individual factors, the environment, and behavior, all contributing to her significant achievements in women's rights.